GE_GERICHTE P/2684/2017 vom 17. August 2017 - GE Cour de justice (2017)
QUALITÉ POUR AGIR ET RECOURIR ; LÉSÉ ; BLANCHIMENT D'ARGENT ; GROUPE DE SOCIÉTÉS ; SOCIÉTÉ FILLE | CP.158; CP.146; CP.305.albis; CPP.118; CPP.115